Are cheese-making properties of dual purpose cattle impaired by highland grazing? A case study using Aosta Red Pied cows - Giovanni Niero; Madeline Koczura; Massimo De Marchi; Sarah Currò; Michael Kreuzer; Germano Turille; Joel Berard (Italian Journal of Animal Science, 2018)
Summer transhumance is often practiced in mountainous farming systems. It includes moving dairy cows from lowland (LO) to highland (HI) pastures during summer. It is known that high genetic merit cows are susceptible to the HI conditions, but it is unclear if this also applies to more adapted, regional cow types. The present study aimed to investigate the effect of HI sojourn on cheese-making properties of Aosta Red Pied cows, a dual purpose cattle type. Milk coagulation properties were measured in the milk of 47 cows before and after transhumance. Sources of variation were investigated using linear mixed models, including parity, site, milking time, the interaction parity × site, milking time × site and milking time × parity. Cow was nested within site, and used as subject for repetition, and sampling date was included as repeated factor. Curd-firming time and curd firmness did not vary between LO and HI, whereas rennet coagulation time was prolonged in HI compared to LO in both primiparous (16.4 vs. 18.5 min) and multiparous cows (17.5 vs. 21.1 min, respectively). The percentage of non-coagulating samples was greater in HI (15.0%) compared to LO (8.5%). The lower milk reactivity to rennet addition in HI seems to be mostly related to the simultaneously increasing somatic cell score. Morning and evening milk were similar in coagulation properties. In conclusion, even indigenous dual purpose cows were affected by HI conditions and the experience the multiparous cows had with the transhumance was not helpful either.